A Closer Look at Laryngeal Nerves during Thyroid Surgery: A Descriptive Study of 584 Nerves. (12th June 2012) - Pradeep, P. V.; Jayashree, B.; Harshita, Skandha S.
Abstract : Morbidity after thyroidectomy is related to injuries to the parathyroids, recurrent laryngeal (RLN) and external branch of superior laryngeal nerves (EBSLN). Mostly these are due to variations in the surgical anatomy. In this study we analyse the surgical anatomy of the laryngeal nerves in Indian patients undergoing thyroidectomy. Materials and Methods . Retrospective study (February 2008 to February 2010). Patients undergoing surgery for benign goitres, T1, T2 thyroid cancers without lymph node involvement were included. Data on EBSLN types, RLN course and its relation to the TZ & LOB were recorded. Results . 404 thyroid surgeries (180 total & 224 hemithyroidectomy) were performed. Data related to 584 EBSLN and RLN were included (324 right sided & 260 left sided). EBSLN patterns were Type 1 in 71.4%, Type IIA in 12.3%, and Type IIB in 7.36%. The nerve was not seen in 4.3% cases. RLN had one branch in 69.34%, two branches in 29.11% and three branches in 1.36%. 25% of the RLN was superficial to the inferior thyroid artery, 65% deep to it and 8.2% between the branches. TZ was Grade 1 in 65.2%, Grade II in 25.1% and Grade III in 9.5%. 31.16% of the RLN passes through the LOB. Conclusions . A thorough knowledge of the laryngeal nerves and anatomical variations is necessary for safe thyroid surgery.